2015
DOI: 10.1117/1.jbo.20.9.096004
|View full text |Cite
|
Sign up to set email alerts
|

Label-free characterization of vitrification-induced morphology changes in single-cell embryos with full-field optical coherence tomography

Abstract: Vitrification is an increasingly popular method of embryo cryopreservation that is used in assisted reproductive technology. Although vitrification has high post-thaw survival rates compared to other freezing techniques, its long-term effects on embryo development are still poorly understood. We demonstrate an application of full-field optical coherence tomography (FF-OCT) to visualize the effects of vitrification on live single-cell (2 pronuclear) mouse embryos without harmful labels. Using FF-OCT, we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Network of membranous organelles, although much less defined than that recorded by our OCM system, was also visualized by a full-field OCM method 12 . In this paper authors proposed that the cytoplasmic signal came mostly from mitochondria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network of membranous organelles, although much less defined than that recorded by our OCM system, was also visualized by a full-field OCM method 12 . In this paper authors proposed that the cytoplasmic signal came mostly from mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike confocal microscopy, which requires fluorescent markers and high numerical aperture and may cause short- and long-term photodamage 7 , OCM is non-invasive and widely applicable in medicine as the primary method for 3D structural and functional imaging in vivo with micrometer resolution and a sampling frequency of up to tens of megahertz 8 . Previous attempts to visualize intracellular structures by OCM imaging involved the full-field OCM technique 9–12 , where in order to reconstruct 3D image of a cell, mechanical scanning along the z-axis is required and several 2D interference images need to be acquired at each depth step. Although those studies revealed some contrast between pronuclei and cytoplasm, they failed, due to the speckle noise, to show fine intracellular structures inside those compartments and did not allow for a high quality 3D cellular reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Cryodamage assessment on a per embryo basis is very challenging due to the invasive nature of the tests available. Very few papers have used OCT to investigate cryodamage in embryos [32,33] and none of them studied blastocyst stage embryos which are widely cryopreserved in both human and animal IVF systems. The SV analysis here described could become a useful tool to quantify the level of damage sustained by cryopreserved embryos within minutes of thawing and without a need for extended culture.…”
Section: Discussionmentioning
confidence: 99%
“…The internal structure of the hybrid collagen/PCL-β-TCP scaffolds were observed at day 14 using a commercially available optical coherence tomography (OCT) system: Telesto OCT Imaging Systems (1310 nm, maximum 92 kHz line rate, 5.5 m axial resolution, Thorlabs Inc., Newton, NJ). Also, the morphology of the cells and lumen formation in the collagen component close to the top surface were investigated after 14 days culture using a custom-built high resolution full-field OCT system (1.5 m axial resolution, 1 m lateral resolution, 580 nm) 36 .…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%